Application of generalized photon-added pair coherent state to quantum teleportation via atom-field entangled channel - Thi Hong Thanh Le; Ngoc Duy Tinh Phan; Minh Duc Truong (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên)
In this paper, we introduce a field-atom entangled state that represents the entanglement over time between a two-level atom and a field in a generalized photon-added pair coherent state in the Jaynes-Cummings model. This entangled state is applied for quantum teleportation of an unknown atomic state from a sender to a receiver that is geographically distant. Accordingly, we use an average fidelity criterion to quantify quantum teleportation processing. The results have shown that the process of teleportation is influenced by parameters such as initial field strength, the amplitude of a state to be teleported, and the number of added photons to two modes of the field. In addition, we also compare the success of teleportation in two cases of the field: the pair coherent state and the generalized photon-added pair coherent state.